Experiences of women researchers in their admission, promotion, and tenure at the National System of Researchers: Tensions and identity strategies - Izquierdo, Isabel; Atristan, Magali (IE Revista de Investigación Educativa de la REDIECH, 2019)
An exploratory study is presented about the experiences of women researchers in their admission, promotion and tenure at the National System of Researchers (SNI, for its Spanish acronym). The tensions they experienced, and the identity strategies they set in motion in that process were analyzed. A biographical method was used, through life stories, by conducting semi-structured interviews to the woman researchers who belong in the levels I, II and III of SNI, in two areas of knowledge.